Atomistic analyses of mechanical properties of graphene sheet - Huang, Jie (2016)
Graphene is a single-layer of carbon atoms forming hexagonal structures connected by sp2 bonds. It has drawn great interest in industry because it possesses extraordinary mechanical, electronic, and thermal properties. However, the fact that it exhibits a band gap of zero and its hydrophobicity require further alteration of its structure to suit the industrial need. Therefore, the main research work of this PhD project is to investigate the effect of structural modification has on the mechanical behaviors of graphene sheet and its interactions with hydrogen atoms using molecular dynamics (MD) simulations. Firstly, the influence of number of layers, chirality, hydrogen coverage, and pattern on the mechanical properties of hydrogenated graphene is investigated. Additionally, the mechanical properties of single and bundled CNS under tensile, compressive, and torsional loading are studied and compared. Last but not least, the thesis details the investigation of the transportation characteristics of hydrogen atoms through CNS.